The Impact of Price and Service Quality on Consumer Satisfaction Mediated by Influencer Marketing: A Study of MSMEs in Palopo City - Lisdayanti, L.; Khaddapi, Muammar; Nadira, Andi (Manunggal Halim Jaya, 2026)
This research aims to analyze the influence of price and service quality on consumer satisfaction through the role of influencer marketing as a mediating variable. The focus of this research is on consumers of Warung Bakso Afni Songka, located in Palopo City. This research employs a quantitative approach, utilizing survey methods. The sample size was set at 100 respondents, although the total population size is unknown. The research instrument was prepared in the form of a questionnaire and measured using a Likert scale. The data analysis technique uses SPSS version 26 software. The research results indicate that price and service quality have a direct and significant positive effect on consumer satisfaction. In addition, influencer marketing is proven to play a mediating role that strengthens the relationship between independent variables and consumer satisfaction. All hypotheses proposed in this research are accepted. These findings contribute to the development of marketing strategies for MSMEs, particularly in the use of influencer marketing to enhance consumer attraction and loyalty. Therefore, MSME owners are advised to focus on competitive pricing strategies, enhance service quality, and optimize collaboration with influencers to deliver sustainable customer satisfaction.